KEKERABATAN BAHASA BUGIS DAN BAHASA KONJO PESISIR DI KABUPATEN BULUKUMBA (LINGUISTIK BANDINGAN HISTORIS) - Wiryatul Jannah; La Ino; Zahrani (Program Studi Sastra Indonesia Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
The main idea of this study is about the kinship relationship of bahasa Bugis and bahasa Konjo Pesisir and also the separation time between those two languages. this study used 200 basic vocabularies by Morris Swadesh as its data, which were then translated into local languages for comparisons. The results showed that from those 200 basic vocabularies that were compared, there were 104 related vocabularies, 39 identical pairs, 36 pairs that had phonemic correspondence and 21 pairs that had one different phoneme. While the separation time between the two languages ranges from 1546 - 1174 years or between 474 - 846 centuries calculated from the present time. Based on the percentage of the related vocabularies and the separation time of those two languages, it can be concluded that bahasa Bugis and bahasa Konjo Pesisir are classified as family, as the percentage of the two languages was 52%.